2007
DOI: 10.1097/01.mcg.0000225589.70706.24
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Irritable Bowel Syndrome in Turkish Population

Abstract: According to our results, in patients complaining of IBS it is of importance to search for a food component. Clinical improvements can be observed after the introduction of an adequate exclusion diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…The rates of IBS increased along with increasing stress levels. A Turkish case-control study (33) showed that depression among IBS cases was significantly much higher (38%) than among the controls (4%). Another recent study from Belgium reported an increased risk of patients with psychological co-morbidity to develop postinfectious IBS (PI-IBS) (34).…”
Section:  Psychological and Psychiatric Factors (Stress Anxiety Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of IBS increased along with increasing stress levels. A Turkish case-control study (33) showed that depression among IBS cases was significantly much higher (38%) than among the controls (4%). Another recent study from Belgium reported an increased risk of patients with psychological co-morbidity to develop postinfectious IBS (PI-IBS) (34).…”
Section:  Psychological and Psychiatric Factors (Stress Anxiety Anmentioning
confidence: 99%
“…Similarly, Zhang et al (35) conducted a meta-analysis of the studies among the Chinese general population and reported that food allergy increased the liability of IBS (OR=2.80, 95% CI: 2.12-3.67). The Turkish case-control study reported that the skin prick test and the mean IgE positivity levels were significantly more among IBS cases than among their controls (33).…”
Section: A) Allergy and Food Hypersensitivitymentioning
confidence: 99%
“…Estimates of prevalence range from 9% to 22% depending upon population group studied [1][2][3][4][5][6][7] . The exact pathophysiology of IBS remains unknown, although various mechanisms including gastrointestinal dismotility and visceral hypersensitivity have been well studied in IBS [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect of that study was the detection of a significant correlation between atopy and increased intestinal permeability, which suggests that at least a subset of IBS patients may have a systemic immunological disorder. Other studies have reported a correlation between asthma, food allergy and IBS [26][27][28][29] , but the role of allergic reactions in the pathophysiology of IBS remains controversial [7,13,27,[29][30][31] . We have previously observed that volunteers with a diagnosis of IBS have reported higher cutaneous reactivity to food antigens than to inhalant allergens, when compared to patients with functional dyspepsia and nor mal controls [30] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation